This I Believe - King, Robert S. (Tufts Archival Research Center, 2006)
Robert King describes how a youthful desire for an automobile led to several crimes and a stretch in jail; however, the time to reflect and the gift of a jalopy from a friend helped him change his lifestyle, and now he believes in a Supreme Being, the oneness of humanity, and the possibility that a universal language could achieve world peace.